Strengthening civic literacy among students through digital literacy in society 5.0 - Muhammad Hendri Nuryadi; Pipit Widiatmaka (Intelektual Pustaka Media Utama, 2023)
The reading index in Indonesia is still relatively low, so many students are victims of fake news that develops on social media. In addition, students have not been able to utilize digital technology as digital literacy to the fullest, so it has implications for the weakness of knowledge about civic literacy. The research design used is a literature review and the type of qualitative research. The research method is literature, while the data collection technique uses document studies and the data analysis used is content analysis. Civic literacy has an important role in facing the era of society 5.0, with the ability of civic literacy, really helps students to participate in realizing the harmony of the life of the nation and state. Society 5.0 has a formidable challenge for higher education if each lecturer does not equip students with civic literacy skills. Strategies to strengthen civic literacy through digital literacy can be carried out effectively, by implementing varied learning methods and using digital-based learning media. Through this, students will be interested in learning, considering that students are a digital native generation who cannot be separated from digital technology. Strengthening civic literacy is very effective by utilizing digital literacy so that every student can adapt to the times, especially society in the 5.0 era.